2017
DOI: 10.1002/pro.3320
|View full text |Cite|
|
Sign up to set email alerts
|

PixelDB: Protein–peptide complexes annotated with structural conservation of the peptide binding mode

Abstract: PixelDB, the Peptide Exosite Location Database, compiles 1966 non-redundant, high-resolution structures of protein-peptide complexes filtered to minimize the impact of crystal packing on peptide conformation. The database is organized to facilitate study of structurally conserved versus non-conserved elements of protein-peptide engagement. PixelDB clusters complexes based on the structural similarity of the peptide-binding protein, and by comparing complexes within a cluster highlights examples of domains that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…For example, for disordered motifs that adopt α-helical structures upon binding, it has been found that increasing the helical propensity of the disordered region confers an increase in affinity for the binding partners [35][36][37][38]. Motif-flanking regions can also contribute with specificity determining information in terms of permissive amino acids that increase the affinity of the interaction [39][40][41][42]. Indeed, a systematic analysis of structures of motif-based interactions revealed that the local sequence context contributes about 20% of the binding and is crucial for determining specificity [40].…”
Section: Affinity and Specificity Of Motif-based Interactionsmentioning
confidence: 99%
“…For example, for disordered motifs that adopt α-helical structures upon binding, it has been found that increasing the helical propensity of the disordered region confers an increase in affinity for the binding partners [35][36][37][38]. Motif-flanking regions can also contribute with specificity determining information in terms of permissive amino acids that increase the affinity of the interaction [39][40][41][42]. Indeed, a systematic analysis of structures of motif-based interactions revealed that the local sequence context contributes about 20% of the binding and is crucial for determining specificity [40].…”
Section: Affinity and Specificity Of Motif-based Interactionsmentioning
confidence: 99%
“…Peptides provide a complementary approach to targeting protein interfaces. Peptide-protein interactions are ubiquitous in nature, where there are many examples of short segments binding to large, structurally complex surfaces (Frappier et al, 2018;Tompa et al, 2014). Peptides can be delivered into cells by chemically modifying them to increase hydrophobicity and hide hydrogen bonds/negative charges (Bird et al, 2016;Rezaei Araghi et al, 2018;Walensky and Bird, 2014), conjugating them to transduction domains (such as cell-penetrating peptides) (Nischan et al, 2015;Qian et al, 2016), or delivering them using nanoparticles (Hiraki et al, 2018;Kumar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The GpsB:PBP interaction interface notably requires no more than three sidechains from any PBP to complex with GpsB. Protein:peptide contacts involving less well-conserved exosites that flank a small core, conserved peptide motif can contribute significantly to the affinity of protein:peptide interactions 43,44 , and the contribution of exosites to affinity may explain why point mutations in Lm PBPA1 and Sp PBP2a have a significant impact using peptide fragments in vitro , but have reduced impact in vivo . For instance, the Lm PBPA1 Arg8Ala mutation had negligible effect in vivo ( Figure 2C , Supplementary Figure 2D ) yet it reduced binding by >15-fold ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%